CEO Role in Operating Performance during the GST and SST Indirect Tax Periods in Malaysia - Sitraselvi Chandren; Mohd Amir Mat Samsudin; Sumaia Ayesh Qaderi; Santhirasegaran Nadarajan (International Journal of Supply Chain Management, 2022)
The paper investigates the CEO role in achieving a desirable operating performance during GST and SST periods. This paper used Ordinary Least Squares (OLS) regression to determine the CEO role in in operating performance during the combined GST and SST periods and individual GST period including SST period for 249 listed firms mainly from manufacturing and service sectors. It is empirically evidence with the support of upper echelon theory assumption that CEO age and CEO education have negative association with operating performance (profitability and liquidity) during the GST and SST periods. The younger CEO has significant role in achieving positive operating performance. The accounting or finance CEO education not in every situation plays critical role in attaining sound operating performance. The CEO ownership has negative influence to profitability and positive influence to liquidity position of the firm. Based on the outcome, CEO ownership should reduce any agency issues by achieving a desirable operating performance (profitability and liquidity). The relationship between CEO type and operating performance are positive for profitably and negative for liquidity. Generally, the CEO whether within the family or outsider require to boost the profitability and liquidity position of firms as these components of operating performance are importance for firm survival and growth even during GST and SST periods. In sum, the outcome reports that CEO role is significant in line with upper echelon theory for effective decision making, managing and making good choices in business operations for achieving a better operating performance during the GST and SST periods